2019
DOI: 10.1002/cctc.201900558
|View full text |Cite
|
Sign up to set email alerts
|

Improved Biocatalytic Activity of the Debaryomyces Species in Seawater

Abstract: Biocatalysis is an environmentally friendly strategy widely used in the chemical and pharmaceutical industries. One of its approaches consists in utilizing whole cells, which usually involves the consumption of large quantities of water. Oceans cover a large part of the Earth's surface, and constitute an important reservoir that can be used as an alternative to freshwater in chemical reactors. This work analyzed the behavior of several yeast halotolerant species belonging to genera Debaryomyces and Schwanniomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…A broader analysis was carried out using all these biocatalysts at different temperatures in freshwater and seawater (Table and Figures 2S–3S). Our previous study found that halotolerant species Debaryomyces and Schwanniomyces showed better thermotolerance in the second medium . This study confirms a similar behavior for all the strains considered when reactions were performed at 45 °C.…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…A broader analysis was carried out using all these biocatalysts at different temperatures in freshwater and seawater (Table and Figures 2S–3S). Our previous study found that halotolerant species Debaryomyces and Schwanniomyces showed better thermotolerance in the second medium . This study confirms a similar behavior for all the strains considered when reactions were performed at 45 °C.…”
Section: Resultssupporting
confidence: 83%
“…Encouraged by our previous results by using seawater as a solvent in reactions catalyzed by Debaryomyces and Schwanniomyces species, we checked the ability of six yeast strains ( Saccharomyces cerevisiae FY86, Pichia fermentans , Pichia glucozyma , Kluyveromyces marxianus , Meyerozyma guilliermondii , and Torulaspora delbrueckii ) to grow in the presence of NaCl, the main component of seawater. Plates with the rich medium usually employed for yeast growth (YPD, see the Experimental section), which contained salt concentrations between 0 and 7.5 % ( w / v ) were used for this purpose.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations